Effect of azithromycin on the growth of Chlorella sorokiniana - Nuñez-Salazar, Yariela (2024)
By employing mixotrophic cultures, the effect of Azithromycin as a contaminant in the culture medium was analyzed, evaluating the growth kinetics of the microalga Chlorella sorokiniana.Three concentrations of azithromycin were evaluated in the culture medium: 10, 15, and 25 ppm. Growth kinetics were assessed by calculating the exponential growth rate, doubling time, and yield rates. Although the viability of Chlorella sorokiniana was significantly reduced by the presence of azithromycin, this microalga managed to grow for up to 18 days in azithromycin concentrations (< 25 ppm) higher than those reported in water treatment plants, which demonstrates its potential to be used in bioremediation strategies. To the best of our knowledge, this is the first report of the growth kinetics of Chlorella sorokiniana at azithromycin concentrations of 10 to 25 ppm.